An Assessment of the Language Learning Attitudes, Learning Strategies, Language Proficiency of First Year College Students - Nelson Julhamid (Philippine Association of Institutions for Research, Inc., 2019)
This descriptive-correlational research described the Language Learning Attitudes (LLA), Language Learning Strategies (LLS) and Language Proficiency (LP) of 120 college students from 4 courses. It employed Lunsford's Standardized LLA Questionnaire, Oxford's (1994) Strategy Inventory of Language Learning (SILL); and Reading Proficiency Test.  It used mean, standard deviation, Pearson r, Multiple Regressions, t-Test of significant difference, and One-Way ANOVA for treatment of data.  This study found out that students are Average in LLA; "Somewhat true of me" in LLS and Poor in reading proficiency. No significant relationship between respondents' LLA and reading proficiency; Very low correlation between respondents' LLS and reading proficiency; Sex and course do not affect students' LLA and do not influence the latter's contribution on reading proficiency except for the inferential level; and Sex does not influence respondents' LLS and reading proficiency except course.  This study hardly provides empirical data to support the theories in LLA and LLS which are supposed to have a significant role in affecting students' reading proficiency. It also denies the role of schema theory in reading by activating learners' prior knowledge to process meaning and concepts from the reading selections.  Variable course may seem to provide empirical support to the extension of the theories in LLS as well as schema theory in reading.